COVID-19 Infection as a Chronic Disease: Factors and Medication Perspectives - Mario G. Balzanelli; Pietro Distratis; Rita Lazzaro; Angelo Cefalo; Giuseppe D’angela; Orrazio Catucci; Davide Palaz- zo; Felice Amatulli; Diego Tomassone; Van H. Pham; et al. (Current Overview on Disease and Health Research Vol. 2, 2022)
Although extremely transmissible due to its highly infectious nature, because a vast percentage of cases are asymptomatic or moderate, self-awareness facilitates the disease’s global spread. To avoid the two viruses infecting each other, public health measures against the Corona virus should minimise the number of persons afflicted with influenza. The successful combination of using antiretroviral therapy and antibiotics in several inflammation in multi organs with supportive therapiesin this case report in region Puglia ASL Taranto, PPI 118- emergency department and pneumonia department in SaintGiuseppe Moscati hospital, Taranto - Italy todevelop achronic disease care model for “POST-COVID-19 “and taking epidemic preventing action for the winter season 2020 is coming. The symptoms associated with acute respiratory failure was confirmed by X-Ray and lung CT scan positive with bilateral ground glass opacity that showed a significant increase in alveolar capillary permeability and subsequent interstitial edema. It was confirmed pulmonary embolism located with a chronic diffuse bronchopathy with emphysematous configurations. It was observed in the right lung the presence of extensive areas of parenchymal consolidation, irregularly distributed, mainly affecting the lower lobe and the apical and dorsal segments of the upper lobe.